2016
DOI: 10.1109/tip.2016.2574992
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Refinement of Possibility Distributions by Learning for Pixel-Based Classification

Abstract: This paper proposes an approach referred as: iterative refinement of possibility distributions by learning (IRPDL) for pixel-based image classification. The IRPDL approach is based on the use of possibilistic reasoning concepts exploiting expert knowledge sources as well as ground possibilistic seeds learning. The set of seeds is constructed by incrementally updating and refining the possibility distributions. Synthetic images as well as real images from the RIDER Breast MRI database are being used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Table 16 for the impoverished datasets, show the advantage of the possibility theory in data modeling compared to the probability theory and the SVM classifier in poor data environments (information incompleteness). Same kind of advantages have been confirmed from results that have been obtained for different kind of applications namely in pattern recognition and image segmentation in the processing of poor-quality images [32,[34][35][36][37].…”
mentioning
confidence: 70%
“…Table 16 for the impoverished datasets, show the advantage of the possibility theory in data modeling compared to the probability theory and the SVM classifier in poor data environments (information incompleteness). Same kind of advantages have been confirmed from results that have been obtained for different kind of applications namely in pattern recognition and image segmentation in the processing of poor-quality images [32,[34][35][36][37].…”
mentioning
confidence: 70%
“…A region grows iteratively by merging neighbourhood pixels to the similar initial seed class regions. For region growing, possibilistic knowledge diffusion (PKD) method is used [22]. In this method, region growing is done with the possibilistic map that is possibilistic knowledge representation instead of grey level.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In the third step, non‐linear normed residual masking is employed on the outcome of the second step for region extraction [21]. In the final step, the possibilistic model is used for region refinement [22]. The refinement process is used to confer sharp edges, outlier, and consistent boundaries to an abnormal region.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method to fuzzy sets for handling fuzzy uncertainty, possibility theory has in recent decades received extensive attention [1][2][3][4][5][6][7][8][9][10][11][12][44][45][46]. It was lately demonstrated that probability and possibility are customized for the measure of randomness and fuzziness, respectively [6].…”
Section: Introductionmentioning
confidence: 99%